INVESTIGATION IN THE POETRY OF MUJIR AL-DEEN IBN TAMIM (684 HIJRI) - Dr. Ali Sahib Issa (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Diagnosis in language: it is derived from the person: they are a group. The person of a person, and the plural of persons, persons and persons. The person: the blackness of a person and others you can see from afar, and everything you see is his body, so I saw his person (1). And the man was diagnosed with annexation; he is a person, any particle. And personified, by conquest, people: rose. IbnSayyidah: The person diagnosed with the thing was diagnosed by people who had litigated, and diagnosed the wound as a tumor. And the characters: Against the decline, and the arrow diagnosed the persons, it is the person: the target (2) and he was diagnosed with it, like me: Something bothered him and bothered him. And as generosity: Increase and increase. And the person: the gaseem, which is Baha, the master, and from the logic: the frowning. And characterize it: It annoyed him, and so-and-so: his walk has come and gone, and with it: his backbiting and the thrower: his arrow may aim. The diagnosed: the different, and the different (3).